Catalyst design strategies for stable electrochemical CO(2)reduction reaction - Choi, Woong; Won, Da Hye; Hwang, Yun Jeong (ROYAL SOC CHEMISTRY, 2020)
The gradual increase in the atmospheric CO(2)concentration is an urgent issue that poses a threat to human beings. Recently, the electrochemical CO(2)reduction reaction (eCO(2)RR) has arisen as a promising and eco-friendly strategy for the storage of electricity from renewable sources as permanent chemical energy, as well as for the conversion of atmospheric CO(2)into value-added chemicals. Among various catalysts, transition metals have been employed as heterogeneous electrocatalysts to yield valuable carbon chemicals such as carbon monoxide, formic acid, ethylene, and ethanol. Recent developments in catalysts and electrochemical devices have boosted catalytic activities and product selectivities, bringing the eCO(2)RR to practically promising levels. However, a lack of study to secure stable catalysts for eCO(2)RR remains a major obstacle for further progress of this technology. This review focuses on efforts to improve the electrochemical stability of catalysts. First, the catalyst deactivation process, including contaminations by metal impurities or carbon derivatives and changes in catalyst morphology during the eCO(2)RR, is discussed to understand the origin of insufficient stability. Next, recent progress in strategies for the preparation of highly stable catalyst systems will be presented. The discussion of valuable approaches that effectively prevent deactivation processes, such as the exclusion of metal impurities, periodic electrochemical activation, and the design of stable catalysts through the manipulation of various factors, allows identification of several clues for long-term stability. We hope that this review will inspire future catalyst design and stimulate the development of new ideas for the improvement of electrochemical stability.
Keywords: CARBON-DIOXIDE REDUCTION; ELECTROCATALYTIC CO2 REDUCTION; GOLD NANOPARTICLES; SUBSURFACE OXYGEN; COPPER ELECTRODES; AU NANOPARTICLES; OXIDATION-STATE; MASS ACTIVITY; ELECTROREDUCTION; EFFICIENT